The carbon stock as indicator of peatland recovery after fire in Central Kalimantan - Muhammad Abdul Qirom; Tri Wira Yuwati; Syaifuddin Syaifuddin (Jurnal GALAM, 2021)
ABSTRACTPeat swamp forest fire was the main cause of the huge carbon stock loss. Forest recovery after fire took a huge cost and long period of time. The aim of this research was to determine the carbon stock on various peat land condition and management intervention and utilize it as bio-indicator for degraded peat swamp forest recovery after fire.  The data was collected from three location representing three sites: after 1997 fire (ex 1997), unburnt secondary forest and area that was severely burnt in 2005 but already re-planted. Measurement was carried out on the vegetation carbon stock namely seedlings, saplings, poles and trees. The carbon stock was determined using 5 sampling plots on secondary forest and 6 plots on other sites. Carbon counting was using allometric equation. The result showed that the carbon stock was affected by the various type and management intervention of the sites especially at the rehabilitation site.  The carbon stock of ex-1997 and secondary forest was not significantly different on all stages of vegetation including the total number. The carbon stock on ex-1997 and secondary forest was 258, 95 Mg/Ha and 254,36 Mg/Ha, respectively. The condition showed that ex-1997 site had the ability to naturally recovered. The rate of recovery can be approached with carbon stock estimation as indicator for peatland recovery after fire. The indicator can be used on sites with no species diversity requirements as recovery factor such as protected or conservation areas. Keywords: natural, allometric, degradation, indicator